The Dividend Trap Score Formulation: a Practical Approach in Dividend Investing - Taruna, Mohammad Sigit; Wahyudi, Sugeng; Abdi, Muhammad Nuskan (Formosa Journal of Applied Sciences, 2024)
Dividends are a key element in investment strategies and are often considered an indicator of a corporate's health and stability. This study aims to develop the Dividend Trap Score (DTS), a quantitative tool for identifying potential dividend traps in stock investments. It distinguishes between Technical and Fundamental Dividend Traps, examining key indicators such as dividend yield ratio, payout ratio, debt levels, and profit trends. Using historical data, the DTS model is tested to assess its accuracy in identifying risky dividend-paying corporates. The findings show that DTS outperforms traditional metrics in evaluating dividend sustainability, offering investors deeper insights and reducing the risk of financial losses. This study contributes to more informed investment strategies by providing a systematic approach to detect dividend-related risks.